An economic crisis? - Andreas Predöhl; Hans-Jürgen Schmahl (Intereconomics, 1966)
According to estimates made by several German economic research institutes, economic growth will slow down also in the coming year. For the first half of 1967 an increase in terms of money by 5% and in real value by 2% is expected. As compared with growth rates in former years this growth is considered a very moderate one. After almost twenty years of uninterrupted prosperity this easing of the cyclical conditions is stirring up in many quarters the deep-rooted fear of an “economic crisis”. Is the Federal Republic of Germany really headed for an economic collapse? To clear up this problem INTERECONOMICS has asked Professor Dr Andreas Predohl, the German Overseas Institute, Hamburg, and Dr Hans-Jurgen Schmahl, the Hamburg Institute for International Economics, Hamburg, for their opinion.
Keywords: 330